Strain improvement and statistical media optimization for enhanced erythritol production with minimal by-products from candida magnoliae mutant R23 - Savergave, Laxman S.; Gadre, Ramchandra V.; Vaidya, Bhalchandra K.; Narayanan, Karthik (Biochemical Engineering Journal, 2011)
Mutants of Candida magnoliae NCIM 3470 were generated by ultra-violet and chemical mutagenesis to enhance erythritol production. The mutants were screened for higher reductase activity on agar plates containing high concentration of glucose and 2,3,5-triphenyl tetrazolium chloride (TTC). One of the mutants named as R23 gave maximum erythritol production, 60.3 g L(-1), compared to 14 g L(-1) of the parent strain. Glucose and yeast extract were identified as critical medium components which decide the ratio of polyols produced, mainly erythritol, mannitol and glycerol. In order to enhance the production of erythritol and to minimize the production of mannitol and glycerol, a four component-five level-three response central-composite-rotatable-design (CCRD) of response surface methodology (RSM) model was used. The optimum medium composition for erythritol production was found to contain (g L(-1)) glucose 238, yeast extract 9.2, KH(2)PO(4), 5.16 and MgSO(4) 0.23. Moreover, erythritol production was studied in a 10 L fermentor in batch and fed-batch mode using RSM optimized medium. In fed-batch fermentation, 87.8 g L(-1) erythritol was produced with 31.1% yield, without formation of any other polyols. Thus present study involving strain improvement followed by media and process optimization resulted in 6.2-fold increase in erythritol production and 3.4-fold increase in the yield. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Candida magnoliae; Erythritol; Fermentation; Metabolite over-production; Modelling; Optimization